Upward, Lateral, or Downward?: Multiple Perspectives on Migrants’ Educational Mobilities - Söhn, Janina (Social Inclusion, 2021)
Education is a major component of individuals’ social status in terms of self-positioning and economic opportunities. Migrants’ qualifications from abroad are often devalued by employers or state institutions. One option to react to such a lack of recognition is the gaining of institutionalized cultural capital in the receiving society. Comparing levels of education attained before and after migration, migrants may move in an upward, lateral, or downward direction. Our study investigates the vertical dimension of transnational educational mobility from multiple perspectives. First, our quantitative analysis of the NEPS (the German National Educational Panel Study) relates the levels of pre- and post-migration education. We critically reflect on how respective results on educational mobility depend on how respondents sort their foreign education into the German system of educational categories and hierarchies used in the survey questionnaire. Second, our qualitative analysis sheds light on several dimensions of migrants’ subjective views and how their educational biographies interact with institutional settings in the receiving society. Exemplarily presented in-depth interviews focus on migrants who pursued educational programs in order to be able to return to the occupations (nursing and economics) they had been trained for abroad, but for which they were denied recognition in Germany. Our findings emphasize that post-migration education is highly ambivalent in terms of in- and exclusion. Individual migrants are caught in the structural tension between academic education as a rather globalized institution and nationally specific educational programs and hierarchies which are often incompatible across borders.